VALU 2010 - SVT exit poll survey parliamentary election 2010 - Holmberg, Sören; Näsman, Per; Wännström, Kent (Sveriges Television, 2014)
This exit poll survey was carried out in connection with the parliamentary election on September 19, 2010.

In VALU - Swedish exit poll surveys - voters leaving polling stations are asked by public service broadcaster Sveriges Television (SVT) to fill in a questionnaire and put it anonymously in a sealed box. After collecting and processing the responses, Sveriges Television is able to present an election forecast and an analysis of the reasons underlying the outcome of the election in it´s Election Night broadcast. The surveys are referred to as VALU, an abbreviation for vallokalsundersökning, Swedish for exit poll survey. The first exit poll survey in Sweden was carried out at the parliamentary election in 1991. Since then similar studies have been carried out in connection with all Parliamentary elections, referendums and elections to the European Parliament.

Voters leaving the polling stations were asked to fill in a questionnaire including questions on: party voted for in the general and local elections; time for decision how to vote; own political opinion in agreement with the opinion of political party voted for; preferred formation of the government after the election; party voted for in the general election 2006; opinion on the Swedish EU membership; placement on a political left-right scale; confidence in Swedish politicians; gender, age, occupational group, union membership and church attendance. The respondents also had to indicate how important a number of items were for the decision how to vote, as well as the importance of the party leader.

Purpose:

Provide analytical support for the election night broadcast on Swedish television during the election night, and for other post-election analysis.

Denna vallokalsundersökning genomfördes i anslutning till riksdagsvalet den 19 september 2010.

En vallokalsundersökning (exit poll) innebär att man frågar ett urval av väljare då de lämnar vallokalen dels vilket parti de röstat på och dels ett antal valsociologiska frågor. Undersökningsmetoden har med framgång använts i ett flertal länder för prognos- och analysändamål. Den första vallokalsundersökningen i Sverige genomfördes vid riksdagsvalet 1991. Liknande undersökningar har sedan dess genomförts i samband med samtliga riksdagsval, folkomröstningar och val till Europaparlamentet.

VALU 2010 innehöll frågor om: vilket parti man röstat på i riksdags- respektive kommunalvalet; om man utnyttjat möjligheten att personrösta; tidpunkt då man bestämt hur man skulle rösta; vilket parti man röstat på i riksdagsvalet 2010; egen placering på en vänster-högerskala; förtroende för svenska politiker; arbetsmarknadsgrupp och medlemskap i facklig organisation; kyrkobesök. Respondenterna fick även ange vilken betydelse partiledaren respektive ett antal valfrågor haft för beslutet hur man skulle rösta. Därutöver fick man ange vilket politiskt block man tyckte hade bäst politik när det gäller svenska ekonomin, sysselsättningen, miljön, sjukvården, sociala välfärden, skola och utbildning, skatterna, och pensionerna.

Syfte:

Ge ett analysunderlag för den valvaka som sändes i Sveriges Television under valkvällen, samt för andra eftervalsanalyser.
VALU 2010 - SVT:s vallokalsundersökning riksdagsvalet 2010
VALU10
Keywords: elections; val; population migration; migration; local government elections; kommunalval; religious attendance; religiöst deltagande; trust; förtroende; exit polls; vallokalsundersökningar; voting; röstning; parliamentary elections; riksdagsval; party identification; partiidentifikation; trade union membership; medlemskap i fackförening; voting behaviour; väljarbeteende; political participation; politiskt deltagande; election data; valdata; government; regering; political parties; politiska partier; political leaders; politiska ledare; electoral issues; valfrågor; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap